A one-step multiplex qPCR assay for simultaneous identification and quantification of Leishmania martiniquensis and Leishmania orientalis/Leishmania chancei and detection and quantification of trypanosomatids in clinical samples - Mano Chonlada; Hirunpatrawong Piyapha; Prasertsilp Patiya; Kaewmee Saowalak; Limprasert Parinda; Siriyasatien Padet; Tantiworawit Adisak; Gatherer Derek; Urbaniak Michael D.; Bates Paul A.; Jariyapan Narissara (Parasite)
Leishmaniasis is one of the most important zoonotic diseases. Recently, Leishmania (Mundinia) martiniquensis, Leishmania (Mundinia) orientalis, and Leishmania (Mundinia) chancei have been reported as new human pathogens. Trypanosomatids, apart from Leishmania spp., such as Crithidia spp., are also occasionally capable of infecting humans. Here, a one-step multiplex qPCR assay for the simultaneous identification and quantification of L. martiniquensis and L. orientalis/L. chancei and detection and quantification of trypanosomatids was developed using ITS1 as the molecular target and human RNase P as the internal control gene. The assay was evaluated using 44 positive residual DNA samples from leishmaniasis patients and 25 negative DNA samples. Results revealed that the limits of detection (LOD) of the assay for L. martiniquensis, L. orientalis, and Crithidia sp. (CLA-KP1) were 1.699 (0.0255), 1.717 (0.0292), and 1.763 (0.0882) fg/reaction (parasite equivalents/reaction), respectively. The assay had high analytical specificity. The mean Cq values of the intra-assays and inter-assays differed by less than 1, indicating the reliability of the assay. Evaluation results revealed that the assay could identify L. martiniquensis and L. orientalis in clinical samples with 100% sensitivity and 100% specificity. In conclusion, the ITS1/human RNase P multiplex qPCR assay offers a rapid and reliable diagnostic tool for identifying and quantifying L. martiniquensis and L. orientalis/L. chancei and detecting and quantifying trypanosomatids in clinical samples within a single reaction. This assay provides an advancement in the diagnostic capabilities for leishmaniasis and trypanosomatid infections, potentially improving patient management and surveillance efforts.